Recurrent anaphylaxis in the United States: time of onset and risk factors. Issue 3 (27th November 2019) - Chaaban, Mohamad R.; Stuart, Jared; Watley, Duncan; Baillargeon, Gwen; Kuo, Yong‐Fang
Abstract : Background: Studies have not yet examined the trends and risk factors of biphasic and recurrent anaphylaxis in the United States using International Classification of Diseases, tenth revision (ICD‐10) CM codes. The goal of this study is to examine the trends of biphasic and recurrent anaphylaxis in all patient care settings (inpatient, outpatient, emergency department, and observation). Methods: We used the Clinformatics database from 2015 to 2017. Our main outcome measure was recurrent anaphylactic events occurring within 1 year after the initial event. We used Cox proportional hazards modeling to assess the factors associated with recurrent anaphylaxis and the Kaplan‐Meier method to estimate time to recurrence. Results: There were a total of 19, 039 patients with incident anaphylaxis in 2016 and, of these, 2017 had a recurrent anaphylaxis event in the 12‐month period after the index date (10.6%). The most common trigger for recurrent anaphylaxis is venom followed by food allergens. Pediatric patients aged <18 years were more likely to develop recurrent anaphylaxis compared with patients aged 18 to 64 years (hazard ratio [HR], 1.53). Patients with allergic rhinitis and asthma were more likely to develop recurrent anaphylaxis compared to those without these comorbidities (HR, 1.15 and 1.27, respectively). Conclusion: This is the first national study using ICD‐10 CM codes looking at rates of biphasic and recurrent anaphylaxis in all patient care settings. Recurrent anaphylaxis is more common in the first 3 days after the initial event, in younger patients (<18 years), and in patients with allergic rhinitis and/or asthma. Physicians need to prescribe epinephrine auto‐injectors and educate their patients about the risk of recurrence.